Review of the electronic book “Dealing with Uncertainties” - Steurer, Michael (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2008)
I review the recent book authored by Manfred Drosg, Dealing with Uncertainties, Springer, Berlin Heidelberg New York 2007, ISBN-10 3-3-540-29606-9, ISBN-13 978-3-540-29606-5, which is the English translation of the author’s German book, Der Umgang mit Unsicherheiten, Facultas Universit¨atsverlag, 2006, ISBN 3-85076-748-5